The reuse of residential spaces as preschool learning environments - Fernandez, Pauline Marie F.
ABSTRACT The study aimed to identify how residential spaces are adapted into preschool learning environments and what spatial issues and concerns arise from such modifications. The research is a qualitative study that utilized a multi-method approach of data gathering. Five schools from Quezon City were chosen through convenience sampling and the owners of the schools were the respondents of the study. The schools included in the study should be recognized by the Department of Education and should only cater to preschool students. The methods employed in the study include interview, observation and photo documentation. Data gathering was completed within five weeks. The study revealed that residential spaces were able to transform into preschool learning environments through major structural and plumbing renovations. Decorative physical changes such as the materials, colors and furniture played a key role in transforming the space into a learning environment. But with these physical changes, the respondents have chosen to incorporate the home atmosphere into their preschool learning environment. Although the Department of Education has provided design guidelines and standard facilities to be implemented in a learning environment, not all schools executed all these requirements. Requirements such as a hand washing facility and exit door measurements were not followed because of the limitations presented by the existing structure which resulted for spatial issues and concerns to occur. The most common issue was the lack of space for programs and the lack of storage space. However, concerns such as the lack of proper fire extinguishing systems and cramped classroom space were noted through the observation but were not urgent concerns of the respondents.